1960
DOI: 10.3382/ps.0390781
|View full text |Cite
|
Sign up to set email alerts
|

Metabolizable Energy of Feed Ingredients for the Growing Chick

Abstract: Hill and Anderson (1958) and have shown that metabolizable energy of a diet is more precisely measured than is productive energy. In an effort to obtain reliable estimates of useful energy content of poultry feeds, a series of studies have been directed toward determining the metabolizable energy of feed ingredients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1
2

Year Published

1970
1970
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(27 citation statements)
references
References 3 publications
3
21
1
2
Order By: Relevance
“…The MEn of blood meal, converted to an air dry basis, was slightly less than that obtained by Oluyemi et al (1976). The efficiency of utilization of the GE in blood meal was slightly less than that of fish meal in our studies but similar to that of fish meal reported by Potter and Matterson (1960).…”
Section: Resultssupporting
confidence: 69%
“…The MEn of blood meal, converted to an air dry basis, was slightly less than that obtained by Oluyemi et al (1976). The efficiency of utilization of the GE in blood meal was slightly less than that of fish meal in our studies but similar to that of fish meal reported by Potter and Matterson (1960).…”
Section: Resultssupporting
confidence: 69%
“…Fuller et al (1966) studied 22 sorghum hybrids, whose tannin contents were determined by the Chang and Fuller (1964) method, and ME by the Potter and Matterson (1960) method. Tannin content ranged from 0.2 to 2.0% and ME from 2617 to 3516 kcal kg-l. Chickens fed on these sorghums showed growth rates negatively related to tannin content, conforming with the previous findings of Chang and Fuller (1964).…”
Section: Metabolizable Energy Valuementioning
confidence: 99%
“…Under similar conditions, sodium dicarbonate removed 77% of the tannins. Tannins can also be removed by treatment of the grain with concentrated ammonia solution (approximately 350 g NH3 kg-l) at room temperature for 7 days (Price and Butler, 1978). Reichert et al (1980) obtained a significant decrease of tannin content by addition of water to reduce sorghum dry matter to 70%, followed by anaerobic incubation at 25°C for 2 days.…”
Section: Physical And/or Chemical Treatmentsmentioning
confidence: 99%
“…C content from one another. The obtained value on a dry matter basis for glucose compares with 3593 (Potter and Matterson, 1960), 3634 (Anderson et al, 1958), 3583 (De Groote, 1969 and 3432 . The determined value for degummed and bleached soybean oil compares with 8290 and 8900, 9200 for degummed, and with the following values for undegummed soybean oil: 8650, 8220, 8940, 8020, , 8370, 8540, , 9170, 9200 (Lewis and Payne, 1966), 9260 (Young, 1961), 9070, 8740, 8930, 9020 (Young and Artman, 1961) and 8450 .…”
Section: Resultsmentioning
confidence: 81%